Q. 13 A3.8( 31 Votes )

# If p(x) = 2+5x th

Put x = 2 in the polynomial

p(2) = 2 + 5× 2

= 2 + 10

= 12

Put x = -2 in the polynomial

p(-2) = 2 + (5× -2)

= 2 – 10

= -8

Put x = 1 in the given polynomial

P(1) = 2 + 5× 1

= 2 + 5

= 7

p(2) + p(-2) – p(1) = 12 – 8 - 7

= -3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Write the correctMHB - Math Part-I

Write the degree MHB - Math Part-I

Write the followiMHB - Math Part-I

Subtract the secoMHB - Math Part-I

Write the followiMHB - Math Part-I

Write the index fMHB - Math Part-I

Add the followingMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I

Write the correctMHB - Math Part-I